The Role of Color and Composition in Miniature Art - Kattaev Nodirjon Saidovich (Zien Journals, 2025)
Eastern miniature art is not just a form of visual art but also a means of reflecting aesthetic taste, cultural values, and historical events. In miniature paintings, color and composition play a crucial role in revealing the semantic meaning of the artwork. This article discusses the analysis of colors and the principles of composition in miniature art.
Keywords: Miniature art; Eastern art; Color symbolism